2021
DOI: 10.3389/fmars.2021.635210
|View full text |Cite
|
Sign up to set email alerts
|

Cu2+ Inhibits the Peroxidase and Antibacterial Activity of Homodimer Hemoglobin From Blood Clam Tegillarca granosa by Destroying Its Heme Pocket Structure

Abstract: Beyond its role as an oxygen transport protein, the homodimer hemoglobin of blood clam Tegillarca granosa (Tg-HbI) has been found to possess antibacterial activity. However, the mechanism of antibacterial activity of Tg-HbI remain to be investigated. In this study, we investigated the effects of Cu2+ on the structure, peroxidase activity, and antibacterial ability of Tg-HbI. Tg-HbI was significantly inactivated by Cu2+ in a non-competitive inhibition manner, following first-order reaction kinetics. The Spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Moreover, De Meulenaere et al (2017) demonstrated that the conserved Glu131 residue at the 3-fold channel had been identified as a critical metal binding site in the Zn-bound structure of ChF. Wang et al also revealed that Hg 2+ ion could coordinate directly with the residues nearby its 3-fold channel of MjFer, largely impeding the entrance of ferrous ions ( Wang et al, 2021 ). Besides, several reports have suggested that the metal ions can conventionally bind to the highly conserved Asp and Glu residues within the 3-fold channel from the marine invertebrates S. constricta ferritin (ScFer) ( Su et al, 2020 ), Phascolosoma esculenta ferritin (PeFer and Fer147) ( Ming et al, 2021 ) and Dendrorhynchus zhejiangensis ferritin (DzFer) ( Huan et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, De Meulenaere et al (2017) demonstrated that the conserved Glu131 residue at the 3-fold channel had been identified as a critical metal binding site in the Zn-bound structure of ChF. Wang et al also revealed that Hg 2+ ion could coordinate directly with the residues nearby its 3-fold channel of MjFer, largely impeding the entrance of ferrous ions ( Wang et al, 2021 ). Besides, several reports have suggested that the metal ions can conventionally bind to the highly conserved Asp and Glu residues within the 3-fold channel from the marine invertebrates S. constricta ferritin (ScFer) ( Su et al, 2020 ), Phascolosoma esculenta ferritin (PeFer and Fer147) ( Ming et al, 2021 ) and Dendrorhynchus zhejiangensis ferritin (DzFer) ( Huan et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The blood clam, Tegillarca granosa , is a marine invertebrate with important economic value that is broadly distributed in the sandy muds of the intertidal zone along the east coast of China and Southeast Asia. The bivalve shellfish T. granosa belongs to the family Arcidae, in the class Bivalvia (phylum Mollusca), and represents one of the rare invertebrates that possess hemoglobin-containing red hemocytes in the hemolymph ( Wang et al, 2021 ). Both ferritin and Cu 2+ ions can play crucial roles in the innate immune defense and antibacterial activity of T. granosa ( Jin et al, 2011 ; Wang et al, 2016 ; Wang et al, 2021 ); however, the interactions between T. granosa ferritin (TgFer) and both iron and copper ions remain unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is widely distributed across the coastal regions of the Indo-Paci c area. T. granosa stands out among invertebrate taxa as possessing red hemocytes within its hemolymph that are enriched with hemoglobin [22]. The blood color of T. granosa is attributed to the abundance of hemoglobin in its hemocytes, resulting in a vibrant red hue [23,24].…”
Section: Introductionmentioning
confidence: 99%